Geo-Metadata Server: Struttura e funzionalit? - Di Bono, Maria Grazia; Martinelli, Massimo; Salvetti, Ovidio (2004)
In the context of the Information System for Italian Research in Antarctica (SIRIA) project, the operating unit of the Institute of Information Science and Technologies has to study and realize a web system for the collection and the management of the metadata on Italian campaigns in Antarctica. The aim of this project report is to illustrate the realization of the Geo-Metadata Server (GMDS), the web system that allows the PNRA researchers to discover all the information about specific data, through a methodology based on an ?Incremental Resource Discovery? mechanism.